A Short Review on Recent Development of Laccase Immobilization on Different Support Materials - Ahmad Jafri, Norsyafiqah Amalina; A. Rahman, Roshanida; Ali, Noorhalieza (Journal of Sustainable Natural Resources, 2021)
Laccase is a bio catalytic agent and multi-copper enzyme containing oxidases that are potentially great for oxidizing large number of phenolic and non-phenolic compounds. However, drawbacks do arise when laccase use in large scale; low in stability, high production cost, non-reusability, sensitive towards denaturing and poor storage ability of free enzymes. These problems lead to the progress in laccase immobilization in order to facilitate the efficient recovery and re-use of the enzyme, thus enabling cost-effective in continuous processes. Apart from discussing on different methods in laccase immobilization such as entrapment, encapsulation and cross-linking in general, we have reviewed a recent development in laccase immobilization on different supports or carriers binding (natural and synthetic). Future works are recommended to focus on innovative strategies on the modified supports to improve the enzyme immobilization as well as sensible entrapment techniques for industrial applications.